Assessing the Global Capital of the Chinese Diaspora - A. V. Afonaseva (Vestnik MGIMO-Universiteta, 2024)
The article focuses on assessing the capital of the global Chinese diaspora (overseas Chinese). Its objective is to estimate the absolute volume of this capital and analyze its potential impact on the economic development of individual countries and regions, including China itself. The author aims to compile and synthesize existing estimates of Chinese diaspora capital, covering studies conducted from 1949 onwards, to examine the methods used in these assessments and to propose an updated approach for evaluating this capital for the period from 2015 to 2023. Additionally, the study seeks to create original maps illustrating the geographical distribution of diaspora capital across countries and regions, both in absolute terms and as a percentage of regional GDP. Furthermore, it identifies key sectors of business activity and evaluates the influence of the Chinese diaspora on industry markets in specific countries and regions. A comparison is also made between the shares of diaspora capital and China’s accumulated outward foreign direct investment relative to the GDP of host countries and regions.The analysis is based on Chinese and international statistical data. The calculation of Chinese diaspora capital for 2015–2023, along with its geographical distribution, draws on data regarding the market capitalization and valuation of major overseas Chinese enterprises. For these calculations, the author identifies eight key countries and regions with significant overseas Chinese business activity (Indonesia, Malaysia, Singapore, Thailand, the Philippines, the United States, Hong Kong, and Fiji). The study estimates the share of large enterprises and SMEs (small and medium-sized enterprises) among overseas Chinese businesses within these locations and globally, adhering to the assumption that 75% of Chinese diaspora capital is concentrated in these eight regions of high business activity.For qualitative evaluation, a comparative analysis method is applied. The current estimate of Chinese diaspora capital, as calculated by the author, is at least $5 trillion (excluding assets in Hong Kong, Macau, and Taiwan unrelated to the Chinese diaspora). This capital spans five continents, holds substantial influence over the economies of more than 50 countries (including China), and serves as a significant external financial resource for China, especially in countries where China’s direct economic involvement is limited.